Measuring skilled emigration rates: the case of small states - Frédéric Docquier; Maurice Schiff (Institute for the Study of Labor (IZA), 2008)
Recent changes in information and communication technologies (ICT) have contributed to a dramatic increase in the integration and interdependence of countries, markets and people. This paper focuses on an increasingly important aspect of globalization, the international movement of people, with emphasis on the mobility of skilled people. This issue is of great concern for the many small states that experience huge brain drain levels.
Keywords: F22; 330; Migration; skilled; brain drain; small states; evidence; Brain Drain; Hochqualifizierte Arbeitskräfte; Internationale Arbeitsmobilität; Messung; Kleinstaat; Welt